Protection and Export Performance in Sub-Saharan Africa - DeRosa, Dean (IMF Working Papers; Working Paper, 1990)
This paper examines the extent and structure of nominal protection in a large sample of Sub-Saharan countries, and provides estimates of the effects of this protection on the exports of these countries. Both tariff rates and the frequency of nontariff barriers are found to be appreciably higher on average in the Sub-Saharan countries than in other developing countries. The empirical estimates, based on simulations of a simple model of trade and real exchange rate adjustment, suggest that protection reduces the value of the sample countries' exports (relative to baseline levels) by between 15 and 33 percent per annum, and inhibits export diversification.